State and Religion in Aceh: The Competences of Religious Education Teachers (Referring to ACT 14, 2005) - Mujiburrahman Mujiburrahman (Graduate Program of Pontianak Institute of Islamic Studies, 2019)
Studies on religious education teacher’s competences in Aceh could not be separated from studies on state’s intervention toward education. State hegemony occurs in the form of regulation formalization which regulates efforts for improving qualification and competence of teachers. The research showed that the presence of Act No. 14, 2005 and the Government Regulation No. 74, 2008 had been used as legal reference to encourage the improvement of Aceh religious education teachers’ qualification and competence. This is a qualitative study in which triangulation in data collection was used. The data was then collected through documentations, observations, and deep interviews. This work emphasizes that improving teachers’ competences in Islamic education system in Aceh was in accordance to and did not contradict with national education system and moreover strengthen the content of Act No. 14, 1005 and Government Regulation No. 74, 2008. Qualification and competence of religious education teachers in Aceh underwent improvement better than previous term. However, teachers experienced that socialization process and implementation of regulation has yet to receive upmost attention. The study also suggests that religious education teachers’ qualifications and competences will significantly contribute to the development of religious education quality, thus Islamic education transforms intently in national and state relations order.